Analisis Penerimaan Followers tentang Klarifikasi Vina Muliana pada Akun Tiktok @Vmuliana dalam konten “Cerita Perjalanan Karierku” - Afifi, Luluk; Amalia, Diana (Universitas Garut, 2024)
This study aims to find out the Acceptance of Followers to Vina Muliana's clarification on the Tiktok account @VMuliana in the content